(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently, the amount of important information and the tremendous sensitivity generated by the interconnectedness of millions of devices (embedded, wireless sensing, radio frequency identification) which are heterogeneous through promising such modern technologies as the IoT. In fact, these small computerized devices have limited capabilities of resources. Therefore, there is an extremely and dire need to protect and secure the sensitive data that generated by these devices taking into account their limited capabilities. However, the traditional coding algorithms like (AES and RSA) are not appropriate for these resource-limited devices due to their high computation cost and large memory consumption. In addition, the integrity and security of data should not be compromised by designing a simple encryption algorithm. Thus, a robust lightweight algorithm for encoding 64-bit data for an 80-bit key is suggested in this paper to provide high hardware security in just six rounds and work on a combination of Feistel and SP architectural methods to increase the encoding complexity. The suggested algorithm is simulated by FELICS and Matlab tools. Different data types such as text and images are used to implement this algorithm. The simulation results show the superiority of the proposed algorithm in different aspects as security, performance, and complexity.